3(-1)+3(0)=-3
-2(-1)+0=2
The answer is the first one
You know that we have to simplify the algebra equation, so first you have to combine x and 2x. X + 2x equals to 3x. Now that we combined x and 2x which makes 3x, we have to do 7 and -8. 7 + -8 which equals to -1. Therefore, the answer to this algebra equation is 3x + -1.
58+24=82 is the correct answer to that question because you subtract 2 from 60 then add that to 6 multiplied by 4
Answer:
(n-10)
Step-by-step explanation:
Jdjdjdhbejdudjkdff
Answer:
Step-by-step explanation:
605/11 = x/5
11x = 3025
x = 275 miles